2016
DOI: 10.1039/c6ob01216g
|View full text |Cite
|
Sign up to set email alerts
|

Natural product inspired design and synthesis of β-carboline and γ-lactone based molecular hybrids

Abstract: β-Carboline and γ-lactone moieties have been selected by nature as privileged scaffolds and display a wide range of pharmacological properties. Following nature, we envisaged the preparation of new β-carboline and γ-lactone based molecular hybrids incorporating both the pharmacophores. In this regard, a water-assisted In-mediated environmentally benign and easy to execute single-step tandem Barbier type allylation-lactonisation process has been devised in order to afford the targeted molecular architectures. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 111 publications
(7 reference statements)
0
21
2
Order By: Relevance
“…However, when the isolated homoallyl alcohol 2aF was treated with p ‐TSA in anhydrous toluene at 100 o C for 5 h, it afforded the desired lactone 3aF (51% yield) as revealed by the spectroscopic data. Interestingly, the NOESY spectrum of 3aF revealed the cis ‐stereochemistry across C‐4 and C‐5 which was different from our recent results . Nevertheless, the failure to develop a one‐pot tandem approach; we were directed to explore other metal catalysts.…”
Section: Resultscontrasting
confidence: 83%
See 1 more Smart Citation
“…However, when the isolated homoallyl alcohol 2aF was treated with p ‐TSA in anhydrous toluene at 100 o C for 5 h, it afforded the desired lactone 3aF (51% yield) as revealed by the spectroscopic data. Interestingly, the NOESY spectrum of 3aF revealed the cis ‐stereochemistry across C‐4 and C‐5 which was different from our recent results . Nevertheless, the failure to develop a one‐pot tandem approach; we were directed to explore other metal catalysts.…”
Section: Resultscontrasting
confidence: 83%
“…To identify the optimum conditions for the synthesis of desired quinoline tethered butyrolactones, 2‐chloroquinoline‐3‐carbaldehyde ( 2a ) and allyl bromide F were identified as the model substrates for Barbier‐Type allylation. In a recent study, we developed an In‐mediated water assisted green methodology for the diastereoselective synthesis of β‐carboline containing butyrolactones with trans ‐stereochemistry . During this previous study, it was observed that water played crucial role during allylation as well as in situ cyclisation and no additive was required.…”
Section: Resultsmentioning
confidence: 99%
“…The study initiated with the synthesis of β‐carboline alkaloid, Kumujian C ( 4 ) and its derivatives ( 5–9 ) which were realized via modification in the previous procedure as depicted in Scheme . The Pictet–Spengler reaction was performed between l ‐tryptophan ( 1 ) and 2,2‐dimethoxyacetaldehyde (60 % aq.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction was observed to be sluggish in aqueous medium possibly due to the solubility problem resulting in the formation of only homoallyl alcohol 5bA in low yield (10%) even after 24 h (Table , entry 1). Our recent findings guided us to explore the advantage of semi‐aqueous medium (THF: H 2 O) for the synthesis of desired prototype, so we performed the reaction in THF: H 2 O (3:2, v/v) as the solvent at room temperature. Interestingly, starting substrate, 3‐formyl 9 H ‐β‐carboline 5b disappeared and the formation of homoallyl alcohol 5bA was observed which started in situ converting into a less polar product 6bA .…”
Section: Resultsmentioning
confidence: 99%
“…The excellent pharmacological potential of these two scaffolds (β‐carboline and γ‐lactone) motivated us to construct a new molecular hybrid containing these two pharmacophores for our anticancer project. In a recent study, we achieved the synthesis of β‐carboline C‐1 substituted γ‐lactones with trans stereochemistry (Scheme ) . The preliminary biological screening studies of these compounds provided us an impetus to expand the scope of library.…”
Section: Introductionmentioning
confidence: 99%